The Effect of Diet and Nutrition on Postprandial Metabolism - Mariotti, François; Dardevet, Dominique (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The postprandial period is the metabolic phase that directly follows the ingestion of a meal. This period is critical to the handling of nutrients to feed the body throughout the whole day but it is also a time of challenge for the body's metabolism, which has to be flexible and adaptable regarding the quantity and the quality of the nutrient intake. Changes in postprandial metabolism have been considered to be potential early markers in the pathophysiological course, finally leading to an increased risk of disease development. This book aimed to broaden and add to the research on the importance of postprandial metabolism in nutrition. The book includes literature reviews that cover the broad state of the art of our knowledge about postprandial metabolism, fine original studies of the complex changes in metabolism, and the physiological processes that are considered to drive the onset of pathogenesis. Finally, a series of examples on how nutrient content (especially proteins, sucrose, and lipids) can influence the postprandial metabolism over a wide range of phenomena operating during the postprandial period and how they could contribute to tipping the body towards adverse health processes.